Columnar Liquid Crystalline Glasses by Combining Configurational Flexibility with Moderate Deviation from Planarity: Extended Triaryltriazines. Issue 24 (17th March 2023) - Nunes da Silva, Fabrícia; Marchi Luciano, Hugo; Stadtlober, Carlos H.; Farias, Giliandro; Durola, Fabien; Eccher, Juliana; Bechtold, Ivan H.; Bock, Harald; Gallardo, Hugo; Vieira, André A.
Abstract: Triply phenanthryl‐ and tetrahelicenyl‐substituted triazine‐hexaalkyl esters with short alkyl chains show glass transitions conveniently above room temperature within the hexagonal columnar liquid crystalline state, resulting in a solid columnar order at room temperature. As the hexagonal columnar mesophase is easily aligned with the director perpendicular to a solid substrate, such glassy columnar liquid matrices are aimed at for the orientation of guest emitters, to obtain anisotropic emission. A condition for face‐on alignment on substrates are attainable melting and clearing temperatures, which is achieved with the moderately nonplanar tetrahelicenyl derivatives in spite of their short alkyl periphery. An unusual phase transition between two columnar mesophases of same hexagonal symmetry, but very different long‐distance regularity of the column lattice, is found in one phenanthryl homolog. Abstract : Three curved aryl arms attached by rotation‐allowing single bonds to a triazine core, together with only short alkyl chains, lead to a glass transition that yields a solid alignable hexagonal columnar mesophase at room temperature.